Communications Skill (Sebuah Analiss terhadap Sistem Komunikasi Menurut Syariat Islam dalam Rangka Pemasaran Sebuah Produk Barang Atau Jasa) - Faujiah, Ani (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
Communication is the main activity of humans in daily life, communication with God, fellow humans, and other creatures. Communication is the capital and key to success in relationships and careers because only by communication a good relationship can be built and fostered. Internet crime (cyber crime) in the form of online fraud (phishing) every year has been known to increase. Which then requires banks to educate customers about the threat of online fraud, increasingly diverse modes also require increasingly sophisticated and secure software protection. This research uses the library research method, which is trying to find understanding of communication that breeds according to Islamic law by taking a phenomenological approach, which is related to the culture of the community in conveying a message or information. Islam has taught its people in good and proper communication by implementing six principles, namely: Sadulan Qaulan, Balighan Qaulan, Masyura Qaulan, Layyina Qaulan, Layina Qaulan, Karima Qaulan and Ma'rufah Qaulan. This study aims to answer the problem How is good communication according to Islamic law? How can Islam in order to guide its people to the marketing of a product or service in a business activity